قراءة في أسباب ومجالات تطوير المنهاج التربوي - علية, سماح; بن ققة, سعاد (دفـاتر المـــــــــــخبـر; No 19 (2018): مجلة دفاتر, 2018)
يشمل المنهاج التربوي جميع الخبرات التعليمية التي تنظمها وتشرف عليها المدرسة، ويمارسها التلاميذ داخل المدرسة وخارجها، بغرض إحداث تغييرات معينة في سلوكهم تحددها الأهداف التربوية المرسومة. ولذلك يرى الكثير من التربويين أن هذا المنهاج التربوي يحتاج دائما وبشكل مستمر ودوري إلى تطوير وتفعيل. وتبعا لذلك وقصد معرفة عوامل ومجالات تطوير المنهاج التربوي عمدنا إلى البحث في مفهوم المنهاج قديما وحديثا، كذلك تطرقنا إلى مفهوم تطوير المنهاج التربوي ،كذلك أسباب تطوير المنهاج التربوي وأهم مجالاته.   الكلمات المفتاحية: المنهاج التربوي، تطوير المنهاج التربوي The educational curriculum includes all the educational experiences organized and supervised by the school, and practiced by students within and outside the school, in order to make certain changes in their behavior determined by the educational goals set. Therefore, many educators confirms that this educational curriculum needs always and continuously to develop and activate. Accordingly, in order to knowing the factors and areas of development of the educational curriculum we meant to research the concept of the curriculum in ancient and modern times. We also discussed the concept of developing the educational curriculum, as well as the reasons for developing the educational curriculum and its most important fields. Keywords: Curriculum, Curriculum Development